Nanocosmetics and Nanomedicines 2011
DOI: 10.1007/978-3-642-19792-5_17
|View full text |Cite
|
Sign up to set email alerts
|

Nanosized and Nanoencapsulated Sunscreens

Abstract: Abstract. Nanotechnology represents an important complement to traditional chromophore-based UV filters. Nanosized metal oxides are widely used due to their broad protection spectrum and reduced skin irritation. These particles are already present in most commercial sunscreen lotions even though their photoreactivity has been highlighted as a potential cause of cytotoxic effects in human skin cells (e.g. fibroblasts, epithelial cells). However, this cytotoxicity is not likely to represent a significant health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
3
0
1
Order By: Relevance
“…A nanoencapsulação dos filtros UV orgânicos tradicionais é a mais recente tecnologia para melhorar a retenção na pele, fotoestabilidade e aumentar o bloqueio UV por parte das moléculas livres. A diminuição da penetração dos filtros orgânicos é promovida pela nanoencapsulação e como resultado ocorre a formação de um filme na superfície da pele (DETONI et al, 2011;Deltreggia, et al, 2019). Dessa forma os agentes protetores ficam nas nanocápsulas e são liberados gradativamente, melhorando sua eficácia, reduzindo o risco de alergia, aumentando a concentração do produto disponível dentro da emulsão.…”
Section: Uma Visão Geral: Fotoproteção No Século XXIunclassified
“…A nanoencapsulação dos filtros UV orgânicos tradicionais é a mais recente tecnologia para melhorar a retenção na pele, fotoestabilidade e aumentar o bloqueio UV por parte das moléculas livres. A diminuição da penetração dos filtros orgânicos é promovida pela nanoencapsulação e como resultado ocorre a formação de um filme na superfície da pele (DETONI et al, 2011;Deltreggia, et al, 2019). Dessa forma os agentes protetores ficam nas nanocápsulas e são liberados gradativamente, melhorando sua eficácia, reduzindo o risco de alergia, aumentando a concentração do produto disponível dentro da emulsão.…”
Section: Uma Visão Geral: Fotoproteção No Século XXIunclassified
“…Being isolated from potential reactive species in their environment, their photostability and their ability to block UV were also optimized. 61 Other applications for nanocapsules include disinfection with the encapsulation of chlorhexidine and the local delivery of indomethacin or minoxidil. 62 …”
Section: Dermal Drug Delivery With Vesicular Systemsmentioning
confidence: 99%
“…Molecular sunscreens like benzophenone-3 (BZ-3) penetrate into skin and induces symptoms of photoaging, photoallergies, phototoxic reactions, and skin irritation. Studies have shown that nanoencapsulation of such traditional UV filters and antipollution agents in organic nanocarriers, potentially help to improve their skin retention, stability, UV blocking action, and anti-pollutant action (Detoni et al, 2011). For instance, the encapsulation of BZ-3 inside PCL and SLNs nanocarriers cause a significant improvement in the stability and sunburn protective action of BZ-3 when compared to BZ-3 alone.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%